Preparation method of homogeneous anion-exchange membrane, homogeneous anion-exchange membrane prepared by same and application of homogeneous anion-exchange membrane
By using the combination of a new quaternary amination polymer and a crosslinker and gradient heating heat treatment technology, the preparation process of homogeneous anion exchange membrane is simplified, and the problems of complex preparation, low mechanical strength and easy swelling in the prior art are solved, and the film preparation with high mechanical strength and stability is achieved.
Patent Information
- Application Number
- CN202510013243.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-03
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-01-03
AI Technical Summary
The existing homogeneous anion exchange membrane preparation method is complex, difficult to operate, low mechanical strength, easy to swell and easy to separate from the support layer, which affects long-term use.
The new quaternary amination polymer is mixed with a crosslinking agent to form a cast film liquid. Through gradient heating heat treatment technology, the film making process is simplified, the crosslinking density and mechanical strength of the film are improved, and the bonding force between the film and the support layer is enhanced.
It has achieved simplified preparation process, reduced production costs, significantly improved the mechanical strength and stability of the film, reduced swelling and separation risks, and extended the service life of the film.
Smart Images

Figure CN119793252A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ion exchange membranes, and in particular to a method for preparing a homogeneous anion exchange membrane, a homogeneous anion exchange membrane prepared thereby, and applications thereof. Background Art
[0002] Electrodialysis achieves desalination, concentration and material separation of solutions by causing the migration of anions and cations in the solution under the action of electric field force. Compared with traditional membrane separation technologies such as reverse osmosis, it has stronger ion selectivity and extremely low pressure, so it has higher efficiency and economy when treating water bodies with high salt content. Ion exchange membranes can be divided into heterogeneous membranes, semi-homogeneous membranes and homogeneous membranes according to their membrane structure. Homogeneous ion exchange membranes have low resistance and excellent electrochemical properties. As a key component in the electrodialysis system, compared with heterogeneous membranes and semi-homogeneous membranes, their structural stability is higher and their performance is more consistent. Therefore, they have great application potential. However, their production process is complicated, the production cost is high, and they have high technical difficulty, which limits their production and promotion.
[0003] The method for preparing homogeneous anion exchange membranes that has been commercially applied at present mainly adopts the base membrane impregnation method, in which a polyolefin base membrane is impregnated in styrene-divinylbenzene monomer, an initiator is added for heating, pressurized polymerization, and then the membrane surface is functionalized (chloromethylation and quaternization) to obtain an anion exchange membrane. Although this method has been widely used, it still has some shortcomings. First, the base membrane impregnation method involves multiple steps, including impregnation, polymerization, functionalization and post-treatment of the base membrane, etc. These steps not only increase the production time, but also require high control conditions between each step, and the operation process is relatively complicated; secondly, due to the limited degree of cross-linking of the membrane during the polymerization process, especially the insufficient tightness between the base membrane and the polymer, the mechanical strength of the anion exchange membrane finally obtained will be low. In the membrane preparation process, the surface functionalization treatment steps such as chloromethylation and quaternization require strict control conditions, and the reaction efficiency is low, and incomplete functionalization is prone to occur, resulting in uneven surface hydrophilicity and ion exchange performance of the membrane, thereby affecting the overall performance of the membrane.
[0004] CN102179186A discloses a homogeneous anion exchange membrane based on in-situ polymerization of monomers and a preparation method thereof. The preparation method comprises the following steps: adding 0.08-0.80 mL of divinylbenzene to every 4 mL of chloromethylstyrene monomer, and then adding 0.5-2 g of phenolphthalein polyether ketone and 0.04-0.20 g of dibenzoyl peroxide or azobisisobutyronitrile, mixing evenly to form a casting solution, coating evenly on a reinforced fabric, heating at 70-130° C. for 6-48 h for in-situ polymerization; immersing the obtained base membrane in a trimethylamine aqueous solution with a mass fraction of 10-40% for quaternization reaction for 6-48 h, washing, and drying (placing in air to dry naturally at room temperature) to obtain a homogeneous anion exchange membrane.
[0005] CN105903357A discloses a homogeneous anion exchange membrane and a preparation method thereof. The method firstly dissolves a polymer enhancer in a mixed solution consisting of p-chloromethylstyrene and styrene, then sequentially adds imidazole small molecules with terminal olefin groups and imidazole small molecules without terminal olefin groups, and stirs evenly to obtain a quaternized membrane liquid; then, the membrane liquid is coated on a coating plate, and heated and cured (dried at 100°C for 12 hours) to obtain an anion exchange membrane.
[0006] It can be seen that the currently disclosed homogeneous anion exchange membranes have at least the following three problems:
[0007] (1) The membrane preparation method is complex and the conditions are uncontrollable: The preparation method of the currently commercialized homogeneous anion exchange membrane includes multiple steps. First, some monomers need to be chloromethylated, then the chloromethylated monomers are polymerized with other monomers, and then the polymers are quaternized, and finally post-processed. This process is complicated, the reaction conditions are harsh, the production cycle is extended, and the operation is difficult. That is, because of its complex preparation route and high technical difficulty, its production and promotion are restricted.
[0008] (2) Poor mechanical strength: The homogeneous anion exchange membrane currently used in commercial applications has low mechanical strength due to the insufficient cross-linking ability of the material during the membrane curing process and the relatively fragile structure during the synthetic cross-linking process. Therefore, it is prone to cracking during long-term use, resulting in performance degradation and a short service life.
[0009] (3) The membrane is easy to swell and separate from the supporting layer: The anion exchange membrane prepared by traditional methods has insufficient adhesion between the coating and the supporting layer, and the poor compatibility of the two materials leads to insufficient bonding. Therefore, during long-term use, the membrane will swell repeatedly, causing the supporting layer and the coating to separate easily, seriously affecting the service life of the ion exchange membrane.
[0010] In view of this, the present invention is proposed. Summary of the invention
[0011] The object of the present invention is to provide a preparation method of a homogeneous anion exchange membrane and a homogeneous anion exchange membrane prepared thereby and its application. The preparation method of the present invention solves the problems that the existing homogeneous anion exchange membrane preparation method is complicated and difficult to control, and the existing homogeneous anion exchange membrane has poor mechanical strength, is easy to swell, is easy to separate from the support layer, and is not conducive to long-term use.
[0012] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0013] In a first aspect, the present invention provides a method for preparing a homogeneous anion exchange membrane, the method for preparing a homogeneous anion exchange membrane comprising the following steps:
[0014] The quaternized polymer, the cross-linking agent and the organic solvent are mixed to obtain a casting solution;
[0015] Applying the casting solution on the support layer to obtain a wet film sheet;
[0016] The wet membrane sheet is heat treated by a gradient temperature increase method to obtain the homogeneous anion exchange membrane.
[0017] The homogeneous anion exchange membrane manufacturing method of the present invention adopts a novel quaternary ammonium polymer material to directly prepare the membrane, and the membrane is formed in one step, with a simple process, convenient operation, and easy control of manufacturing conditions. The homogeneous anion exchange membrane of the present invention adopts a combination of a novel quaternary ammonium polymer material and a cross-linking agent, which is directly dissolved in an organic solvent to form a casting liquid, and the cross-linking density of the membrane is improved by optimizing the heat treatment process, thereby enhancing the toughness and tensile strength of the membrane, and the added lining mesh further improves the mechanical strength of the homogeneous anion exchange membrane. The active sites of the material selected by the preparation method of the present invention are evenly distributed, and the cross-linking density of the membrane is increased by adding a cross-linking agent, thereby enhancing the structural stability of the membrane, reducing its swelling, and improving the compatibility of the coating liquid with the support layer. At the same time, a heat treatment method of first gradient heating and then gradient cooling is used to prevent the deformation and cracking of the membrane, so that the coating and the support layer are more difficult to separate.
[0018] More specifically, the present invention adopts the above preparation method, which has at least the following two advantages:
[0019] (1) The present invention adopts a method for directly preparing membranes using a new type of quaternary ammonium polymer, eliminating the traditional method of first chloromethylating the material monomer on the production line, then polymerizing and then quaternizing it, reducing the membrane preparation process, simplifying the operation, and facilitating automatic control. The new type of quaternary ammonium polymer is prepared by first quaternizing, avoiding the common quaternization position instability during the post-quaternization treatment process, which is prone to chain breaking, branching and side reactions, and making the quaternary ammonium group distribution in the polymer more uniform. The electric field distribution inside the prepared membrane is more consistent, thereby enhancing the selective transmission ability of ions; the uniform distribution of quaternary ammonium groups reduces the risk of swelling of the membrane in water, allowing it to maintain a stable size and shape under wet or working conditions, thereby increasing the life of the membrane.
[0020] (2) Gradient heat treatment process: A unique gradient heating and cooling heat treatment process and time control are used to make the cross-linking and curing of the membrane more uniform, significantly improving the mechanical strength and conductivity of the membrane. Too high a temperature will lead to polymer degradation or excessive cross-linking, weaken the activity of the sulfonic acid group, reduce the ion exchange performance, and also cause the lining to deform, reducing the product qualification rate; too low a temperature will lead to insufficient cross-linking and insufficient mechanical properties of the membrane. Therefore, through this gradual heat treatment method, the uniformity of cross-linking is ensured, the formation of internal stress is effectively controlled, the deformation of the lining is reduced, the swelling of the membrane is reduced, and the long-term stability of the membrane is enhanced. At the same time, too long a heat treatment time will lead to excessive curing of the membrane and reduced flexibility; too short a time will lead to insufficient cross-linking and unstable membrane structure. The time is controlled within 10 to 120 minutes to balance the cross-linking effect and the flexibility of the membrane, ensuring mechanical strength and conductivity.
[0021] Preferably, the casting solution comprises the following components by mass percentage: 10-60% of quaternary ammonium polymer, 0.1-10% of cross-linking agent, and the balance is organic solvent.
[0022] Preferably, the quaternized polymer is selected from any one of quaternized polyetherketone, quaternized polyetheretherketone, quaternized polyetherketoneketone, quaternized polyetheretherketoneketone, quaternized polyetherketoneetherketoneketone, quaternized polyetherketoneetherketoneketone, quaternized polysulfone, quaternized polyethersulfone, quaternized polyphenylsulfone or quaternized polyarylsulfone, or a combination of at least two thereof.
[0023] Preferably, the quaternization degree of the quaternized polymer is 10-60%.
[0024] Preferably, the cross-linking agent is selected from any one or a combination of at least two of polyvinyl alcohol, polyvinyl pyrrolidone, divinyl benzene, formaldehyde, maleic acid or glutaraldehyde.
[0025] Preferably, the organic solvent is selected from any one of dimethyl sulfoxide, 1,2-dichloroethane, N,N-dimethylformamide, N,N-dimethylacetamide, N-methyl-2-pyrrolidone, dichloromethane or chloroform, or a combination of at least two thereof.
[0026] Preferably, in the process of preparing the casting solution, the mixing temperature is 30 to 50° C., and the mixing time is 12 to 48 hours.
[0027] Preferably, the support layer comprises any one of mesh, non-woven fabric or porous membrane.
[0028] Preferably, the material of the support layer is selected from any one of polypropylene, polyethylene, polyvinyl chloride, polytetrafluoroethylene, polyethylene terephthalate, nylon or glass fiber.
[0029] Preferably, the support layer has a thickness of 10 to 200 μm.
[0030] Preferably, the thickness of the wet film applied on the support layer is 0.2-1.0 mm.
[0031] Preferably, the gradient temperature increase procedure is:
[0032] First raise the temperature to 50-80℃ and keep it for 10-15min, then raise the temperature to 80-100℃ and keep it for 5-10min, and finally raise the temperature to 110-140℃ and keep it for 1-5min.
[0033] Preferably, after the heat treatment is completed, the method further comprises: performing post-treatment on the heat-treated membrane by using a gradient cooling method.
[0034] Preferably, the gradient cooling procedure is:
[0035] First cool down to 80-100℃ and keep warm for 5-10 minutes, then cool down to 50-80℃ and keep warm for 1-5 minutes.
[0036] In a second aspect, the present invention provides a homogeneous anion exchange membrane, wherein the homogeneous anion exchange membrane is prepared by the method for preparing a homogeneous anion exchange membrane as described in the first aspect.
[0037] Preferably, the thickness of the homogeneous anion exchange membrane is 0.1-0.3 mm.
[0038] Preferably, the resistance of the homogeneous anion exchange membrane is 2 to 5 Ω·cm 2 .
[0039] Preferably, the water content of the homogeneous anion exchange membrane is less than 25%.
[0040] Preferably, the ion exchange capacity of the homogeneous anion exchange membrane is greater than 1.8 mmol / g.
[0041] Preferably, the bursting strength of the homogeneous anion exchange membrane is greater than 0.50 MPa.
[0042] In a third aspect, the present invention provides a use of the homogeneous anion exchange membrane as described in the second aspect in preparing an anion exchange membrane for electrodialysis.
[0043] Compared with the prior art, the present invention has the following beneficial effects:
[0044] (1) Simplify the preparation process and reduce costs: The method for preparing a homogeneous anion exchange membrane used in the present invention uses a new quaternary ammonium polymer mixed with a cross-linking agent as a membrane precursor, dissolves it in an organic solvent and then coats it, and forms a membrane after gradient heat treatment. The operation process is simple and easy to control automatically. At the same time, the new quaternary ammonium polymer is directly used, which omits the complicated functionalization steps in the traditional method and simplifies the preparation process. Combined with the optimized coating and heat treatment process, the operation difficulty and cycle in production are reduced, while the production cost is reduced and the production efficiency is improved.
[0045] (2) Enhanced mechanical strength and improved long-term stability: Gradient heat treatment enables the membrane to form a high-density cross-linked network, which significantly improves the mechanical strength of the membrane, reduces the risk of damage in practical applications, and extends the service life of the membrane.
[0046] (3) Significantly reduce swelling: The gradient heat treatment process effectively enhances the cross-linking degree of the membrane. Through the uniform cross-linking structure and precise material ratio, the swelling phenomenon of the membrane prepared by the present invention in the water environment is effectively controlled, the swelling is reduced, and the dimensional stability of the membrane in the water environment is ensured. The size and performance stability of the membrane are ensured, which makes the membrane more stable under long-term use conditions and suitable for long-term application.
[0047] (4) Strong bonding between the membrane and the support layer: The coating technology and heat treatment process ensure the strong bonding between the membrane and the support layer, avoiding the problem of separation between the membrane and the support layer during use, significantly enhancing the bonding between the membrane and the support layer, and reducing the risk of separation between the membrane and the support layer. At the same time, the ion exchange groups of the membrane are evenly distributed, which improves the ion exchange performance and selectivity of the membrane, thereby improving the efficiency and stability of the membrane in the separation and electrochemical processes.
[0048] (5) Environmental protection and economy: The simplified preparation process and direct use of quaternized polymers reduce solvent and energy consumption, lower production costs, and make the process more environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0050] Figure 1 The present invention provides a flow chart for preparing a homogeneous anion exchange membrane. DETAILED DESCRIPTION
[0051] Unless otherwise defined herein, scientific and technological terms used in conjunction with the present invention shall have the meanings commonly understood by those of ordinary skill in the art. The meaning and scope of the terms should be clear, however, in the case of any potential ambiguity, the definitions provided herein take precedence over any dictionary or external definitions. In this application, unless otherwise stated, the use of "or" means "and / or". In addition, the use of the term "including" and other forms is non-limiting.
[0052] It should be noted that specific details are described in the following description to facilitate a full understanding of the present invention. However, the present invention can be implemented in a variety of other ways different from those described herein, and those skilled in the art can make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0053] The embodiments of the present invention will be described in detail below in conjunction with the embodiments and examples, but it will be appreciated by those skilled in the art that the following embodiments and examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. If specific conditions are not specified, proceed according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0054] In a first aspect, the present invention provides a method for preparing a homogeneous anion exchange membrane, such as Figure 1 As shown, the preparation method of the homogeneous anion exchange membrane comprises the following steps:
[0055] The quaternized polymer, the cross-linking agent and the organic solvent are mixed to obtain a casting solution;
[0056] Applying the casting solution on the support layer to obtain a wet film sheet;
[0057] The wet membrane sheet is heat treated by a gradient temperature increase method to obtain the homogeneous anion exchange membrane.
[0058] In the present invention, a preparation method of a homogeneous anion exchange membrane is provided. The preparation method uses a novel quaternized polymer as a membrane precursor, dissolves it in an organic solvent, and then adds a certain amount of a cross-linking agent to form a membrane, and then performs a gradient heating-gradient cooling heat treatment to form a membrane. The operation process is simple and easy to automatically control. After the heat treatment is completed, a high-strength, swelling-resistant homogeneous anion exchange membrane is obtained, ensuring its long-term stability in water treatment and electrochemical applications.
[0059] First, in the process of preparing the casting solution, the present invention dissolves the novel quaternary aminated polymer and the cross-linking agent in an organic solvent according to a specific ratio, and defoams to obtain a uniform casting solution. This step ensures the uniform distribution of the membrane material, avoids the multi-step functionalization operation in the traditional method, and improves the simplicity of the preparation process. At the same time, the preparation process is simplified and the investment in production equipment is reduced: the novel quaternary aminated polymer is directly used, and the post-functionalization steps such as chloromethylation and quaternization on the production line in the traditional method are avoided, so that the preparation process is simpler and more efficient, and the production cycle is shortened by reducing the process steps, and the equipment investment is reduced at the same time. In addition, the novel quaternary aminated polymer is used as a raw material, so that the anion exchange group is evenly distributed in the membrane, ensuring that the membrane has a higher ion exchange capacity.
[0060] Second, the present invention then evenly coats the casting solution on the support layer, and controls the thickness and coating uniformity of the film through precise scraping technology. This step not only improves the structural integrity of the film, but also enhances the bonding force between the film and the support layer, avoiding the problem of easy separation of the film layer.
[0061] Third, the present invention then uses a gradient temperature increase method to heat treat the wet film sheet to promote the curing and cross-linking of the film. During the temperature increase process, the film material gradually cross-links to form a stable structure, and the generation of stress is avoided by the gradual change of temperature. This treatment significantly enhances the mechanical strength of the film and reduces its swelling. At the same time, the gradient heat treatment and the addition of a support layer are used to enhance the cross-linking degree of the film, so that it forms a stable network structure, more significantly improve the mechanical strength and stability of the film, reduce the degree of deformation of the film, and reduce the damage of the film.
[0062] As an optional implementation, the casting solution comprises the following components by weight percentage: 10-60% of quaternary ammonium polymer, 0.1-10% of cross-linking agent, and the balance is organic solvent.
[0063] As an optional embodiment, based on the total mass of the casting solution as 100%, the content of the quaternary ammonium polymer is 10-60%, for example, it can be 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%, 45%, 50%, 55%, 60%, etc.
[0064] As an optional embodiment, based on the total mass of the casting solution as 100%, the content of the cross-linking agent is 0.1-10%, for example, it can be 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.2%, 1.4%, 1.5%, 1.6%, 1.8%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, etc.
[0065] In the present invention, the ratio of film-making raw materials is optimized to improve the performance of the membrane: the quaternization ratio of the new quaternized polymer is controlled between 10 and 60%, ensuring that the membrane has good mechanical strength and dimensional stability while having efficient ion conduction; the cross-linking agent concentration is optimized at 0.1 to 10%, so that the membrane has better conductivity, mechanical strength and flexibility, further reducing the swelling phenomenon of the membrane and extending the service life of the membrane; the solvent ratio is optimized at 70 to 90%, ensuring that the casting liquid has a suitable viscosity, is evenly coated, has a high density of the membrane layer, and the membrane surface is flat and smooth without defects after the solvent evaporates.
[0066] As an optional embodiment, the quaternized polymer is selected from any one of quaternized polyetherketone, quaternized polyetheretherketone, quaternized polyetherketoneketone, quaternized polyetheretherketoneketone, quaternized polyetherketoneetherketoneketone, quaternized polyetherketoneetherketoneketone, quaternized polysulfone, quaternized polyethersulfone, quaternized polyphenylsulfone or quaternized polyarylsulfone, or a combination of at least two thereof.
[0067] As an optional embodiment, the quaternization degree of the quaternized polymer is 10-60%, for example, it can be 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, etc.
[0068] As an optional embodiment, the cross-linking agent is selected from any one or a combination of at least two of polyvinyl alcohol, polyvinyl pyrrolidone, divinyl benzene, formaldehyde, maleic acid or glutaraldehyde.
[0069] In the present invention, the above-selected raw materials for making membranes (quaternary aminated polymers) all have the characteristics of high stability and high strength, and the addition of the above-mentioned cross-linking agent makes the entire material structure more compact and stable, so the homogeneous anion exchange membrane has the advantage of high mechanical strength. And it can be coated on a supporting mesh to further increase its mechanical strength. In addition, the cross-linking agent can form a tighter structure between the molecular chains of the polymer, thereby reducing the influence and damage on the polymer molecular chains due to the external environment.
[0070] As an optional embodiment, the organic solvent is selected from any one of dimethyl sulfoxide, 1,2-dichloroethane, N,N-dimethylformamide, N,N-dimethylacetamide, N-methyl-2-pyrrolidone, dichloromethane or chloroform, or a combination of at least two thereof.
[0071] As an optional embodiment, in the process of preparing the casting solution, the mixing temperature is 30-50°C, for example, it can be 30°C, 32°C, 34°C, 35°C, 36°C, 38°C, 40°C, 42°C, 44°C, 45°C, 46°C, 48°C, 50°C, etc., and the mixing time is 12-48h, for example, it can be 12h, 13h, 14h, 15h, 16h, 17h, 18h, 20h, 22h, 24h, 25h, 26h, 28h, 30h, 32h, 33h, 34h, 35h, 36h, 38h, 40h, 42h, 44h, 45h, 46h, 48h, etc.
[0072] As an optional embodiment, the support layer includes any one of mesh cloth, non-woven fabric or porous membrane.
[0073] As an optional embodiment, the material of the support layer is selected from any one of polypropylene, polyethylene, polyvinyl chloride, polytetrafluoroethylene, polyethylene terephthalate, nylon or glass fiber.
[0074] As an optional embodiment, the thickness of the support layer is 10 to 200 μm, for example, it can be 10 μm, 20 μm, 40 μm, 50 μm, 60 μm, 80 μm, 100 μm, 120 μm, 140 μm, 150 μm, 160 μm, 180 μm, 200 μm, etc.
[0075] As an optional embodiment, the thickness of the wet film applied on the support layer is 0.2-1.0 mm, for example, 0.2 mm, 0.3 mm, 0.4 mm, 0.5 mm, 0.6 mm, 0.7 mm, 0.8 mm, 0.9 mm, 1.0 mm, etc.
[0076] As an optional embodiment, the program of the gradient temperature increase is:
[0077] First raise the temperature to 50-80℃ and keep it for 10-15min, then raise the temperature to 80-100℃ and keep it for 5-10min, and finally raise the temperature to 110-140℃ and keep it for 1-5min.
[0078] In the first stage of the gradient heating process, the insulation temperature of the heat treatment is 50-80°C, for example, it can be 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, etc.; the insulation time of the heat treatment is 10-15min, for example, it can be 10min, 11min, 12min, 13min, 14min, 15min, etc.
[0079] In the second stage of the gradient heating process, the insulation temperature of the heat treatment is 80-100°C, for example, it can be 80°C, 85°C, 90°C, 95°C, 100°C, etc.; the insulation time of the heat treatment is 5-10min, for example, it can be 5min, 6min, 7min, 8min, 9min, 10min, etc.
[0080] In the third stage of the gradient heating process, the insulation temperature of the heat treatment is 110-140°C, for example, it can be 80°C, 85°C, 90°C, 95°C, 100°C, etc.; the insulation time of the heat treatment is 1-5min, for example, it can be 1min, 2min, 3min, 4min, 5min, etc.
[0081] As an optional embodiment, during the gradient heating process, the second stage is heated by 20-30°C relative to the first stage, for example, 20°C, 21°C, 22°C, 23°C, 24°C, 25°C, 26°C, 27°C, 28°C, 29°C, 30°C, etc.; the third stage is heated by 20-40°C relative to the second stage, for example, 20°C, 21°C, 22°C, 23°C, 24°C, 25°C, 26°C, 27°C, 28°C, 29°C, 30°C, 31°C, 32°C, 33°C, 34°C, 35°C, 36°C, 37°C, 38°C, 39°C, 40°C, etc.
[0082] As an optional embodiment, during the gradient heating process, the processing time of the second stage is reduced by 5 to 8 minutes relative to that of the first stage, and may be, for example, 5 minutes, 5.5 minutes, 6 minutes, 6.5 minutes, 7 minutes, 7.5 minutes, 8 minutes, etc.; the processing time of the third stage is reduced by 2 to 4 minutes relative to that of the second stage, and may be, for example, 2 minutes, 2.5 minutes, 3 minutes, 3.5 minutes, 4 minutes, etc.
[0083] As an optional implementation, after the heat treatment is completed, the method further includes: performing post-treatment on the heat-treated membrane by using a gradient cooling method.
[0084] In the present invention, the gradient temperature increase heat treatment is completed, and the membrane after the heat treatment is preferably post-treated by gradient cooling. This cooling method is more conducive to forming a stable membrane structure. The generation of stress is avoided by the gradual change of cooling. This treatment can further enhance the mechanical strength of the membrane and reduce its swelling.
[0085] As an optional implementation, the gradient cooling procedure is:
[0086] First cool down to 80-100℃ and keep warm for 5-10 minutes, then cool down to 50-80℃ and keep warm for 10-15 minutes.
[0087] In the first stage of the gradient cooling process, the insulation temperature of the heat treatment is 80-100°C, for example, it can be 80°C, 85°C, 90°C, 95°C, 100°C, etc.; the insulation time of the heat treatment is 5-10min, for example, it can be 5min, 6min, 7min, 8min, 9min, 10min, etc.
[0088] In the second stage of the gradient cooling process, the insulation temperature of the heat treatment is 50-80°C, for example, it can be 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, etc.; the insulation time of the heat treatment is 1-5min, for example, it can be 1min, 2min, 3min, 4min, 5min, etc.
[0089] As an optional embodiment, during the gradient cooling process, the second stage is cooled by 20-40°C relative to the first stage, for example, 20°C, 21°C, 22°C, 23°C, 24°C, 25°C, 26°C, 27°C, 28°C, 29°C, 30°C, 31°C, 32°C, 33°C, 34°C, 35°C, 36°C, 37°C, 38°C, 39°C, 40°C, etc.
[0090] As an optional embodiment, during the gradient cooling process, the processing time of the second stage is reduced by 5 to 8 minutes relative to the first stage cooling, for example, it can be 5 minutes, 5.5 minutes, 6 minutes, 6.5 minutes, 7 minutes, 7.5 minutes, 8 minutes, etc.
[0091] In a second aspect, the present invention provides a homogeneous anion exchange membrane, wherein the homogeneous anion exchange membrane is prepared by the method for preparing a homogeneous anion exchange membrane as described in the first aspect.
[0092] As an optional embodiment, the thickness of the homogeneous anion exchange membrane is 0.1-0.3 mm, for example, it can be 0.1 mm, 0.12 mm, 0.14 mm, 0.15 mm, 0.16 mm, 0.18 mm, 0.2 mm, 0.22 mm, 0.24 mm, 0.25 mm, 0.26 mm, 0.28 mm, 0.3 mm, etc.
[0093] As an optional embodiment, the resistance of the homogeneous anion exchange membrane is 2 to 5 Ω·cm 2 , for example, it can be 2Ω·cm 2 , 2.2Ω·cm 2 , 2.4Ω·cm 2 , 2.6Ω·cm 2 , 2.8Ω·cm 2 、3Ω·cm 2 、3.2Ω·cm 2 、3.4Ω·cm 2 、3.5Ω·cm 2 、3.6Ω·cm 2 、3.8Ω·cm 2 , 4Ω·cm 2 , 4.2Ω·cm 2 , 4.4Ω·cm 2 , 4.6Ω·cm 2 、4.8Ω·cm 2 , 5Ω·cm 2 wait.
[0094] As an optional embodiment, the water content of the homogeneous anion exchange membrane is below 25%, for example, it can be 25%, 24%, 23%, 22%, 21%, 20%, 19%, 18%, 17%, 16%, 15%, etc.
[0095] As an optional embodiment, the ion exchange capacity of the homogeneous anion exchange membrane is above 1.8mmol / g, for example, it can be 1.8mmol / g, 1.82mmol / g, 1.84mmol / g, 1.85mmol / g, 1.86mmol / g, 1.88mmol / g, 1.9mmol / g, 1.92mmol / g, 1.94mmol / g, 1.95mmol / g, 1.96mmol / g, 1.98mmol / g, 2mmol / g, 2.02mmol / g, 2.04mmol / g, 2.05mmol / g, 2.06mmol / g, 2.08mmol / g, 2.1mmol / g, 2.12mmol / g, 2.14mmol / g, 2.15mmol / g, etc.
[0096] As an optional embodiment, the bursting strength of the homogeneous anion exchange membrane is greater than 0.50 MPa.
[0097] In a third aspect, the present invention provides a use of the homogeneous anion exchange membrane as described in the second aspect in preparing an anion exchange membrane for electrodialysis.
[0098] The present invention is further described below by means of specific examples and comparative examples. However, it should be understood that these examples are only used for more detailed description and should not be construed as limiting the present invention in any form.
[0099] Example 1
[0100] This embodiment provides a method for preparing a homogeneous anion exchange membrane, and the method for preparing a homogeneous anion exchange membrane comprises the following steps:
[0101] (1) 200 g of quaternized polyphenylsulfone with a quaternization degree of 20%, 20 g of polyvinyl alcohol and 2000 g of N,N-dimethylacetamide were mixed and stirred at 40° C. for 20 h until they were completely dissolved to obtain a casting solution;
[0102] (2) Take 100 mL of casting solution and spray it evenly on the PET mesh (area 1000 cm 2 , thickness of 40 μm), to obtain a wet film;
[0103] (3) placing the wet membrane sheet in an oven, setting a gradient heating and cooling program for curing, and then taking it out of the oven and cooling it to room temperature to obtain the homogeneous anion exchange membrane;
[0104] The curing treatment is as follows: heating to 50°C and keeping warm for 15 minutes, heating to 80°C and keeping warm for 7 minutes, heating to 120°C and keeping warm for 5 minutes; then cooling to 80°C and keeping warm for 7 minutes, and cooling to 50°C and keeping warm for 2 minutes.
[0105] Example 2
[0106] This embodiment provides a method for preparing a homogeneous anion exchange membrane, and the method for preparing a homogeneous anion exchange membrane comprises the following steps:
[0107] (1) 200 g of quaternized polyethersulfone with a quaternization degree of 30%, 20 g of polyvinyl pyrrolidone and 2000 g of N,N-dimethylformamide were mixed, and stirred at 40° C. for 20 h until they were completely dissolved to obtain a casting solution;
[0108] (2) Take 100 mL of the casting solution and spray it evenly on the PET nonwoven fabric (area 1000 cm 2 , thickness of 80 μm), to obtain a wet film;
[0109] (3) placing the wet membrane sheet in an oven, setting a gradient heating and cooling program for curing, and then taking it out of the oven and cooling it to room temperature to obtain the homogeneous anion exchange membrane;
[0110] The curing treatment is as follows: heating to 65°C and keeping warm for 12 minutes, heating to 90°C and keeping warm for 6 minutes, heating to 110°C and keeping warm for 3 minutes; then cooling to 90°C and keeping warm for 6 minutes, and cooling to 65°C and keeping warm for 5 minutes.
[0111] Example 3
[0112] This embodiment provides a method for preparing a homogeneous anion exchange membrane, and the method for preparing a homogeneous anion exchange membrane comprises the following steps:
[0113] (1) 200 g of quaternized polyetheretherketone with a quaternization degree of 40%, 20 g of divinylbenzene and 2000 g of dimethyl sulfoxide were mixed, and stirred at 40° C. for 20 h until they were completely dissolved to obtain a casting solution;
[0114] (2) Take 100 mL of the casting solution and spray it evenly on the PET nonwoven fabric (area 1000 cm 2 , thickness of 70 μm), to obtain a wet film;
[0115] (3) placing the wet membrane sheet in an oven, setting a gradient heating and cooling program for curing, and then taking it out of the oven and cooling it to room temperature to obtain the homogeneous anion exchange membrane;
[0116] The curing treatment is as follows: heating to 80°C and keeping warm for 10 minutes, heating to 100°C and keeping warm for 5 minutes, heating to 140°C and keeping warm for 1 minute; then cooling to 100°C and keeping warm for 5 minutes, cooling to 80°C and keeping warm for 1 minute.
[0117] Example 4
[0118] The present embodiment provides a method for preparing a homogeneous anion exchange membrane, which differs from the embodiment 1 only in that the ratio of the casting solution in step (1) is different: specifically, 100 g of quaternized polyphenylsulfone with a quaternization degree of 20%, 20 g of polyvinyl alcohol and 2000 g of N,N-dimethylacetamide are mixed, stirred at 40°C for 20 hours, and the mixture is completely dissolved to obtain a casting solution; the other steps are consistent with the embodiment 1.
[0119] Example 5
[0120] The present embodiment provides a method for preparing a homogeneous anion exchange membrane, which differs from the embodiment 1 only in that the ratio of the casting solution in step (1) is different: specifically, 500 g of quaternized polyphenylsulfone with a quaternization degree of 20%, 20 g of polyvinyl alcohol and 2000 g of N,N-dimethylacetamide are mixed, stirred at 40°C for 20 hours, and the mixture is completely dissolved to obtain a casting solution; the other steps are consistent with the embodiment 1.
[0121] Example 6
[0122] This embodiment provides a method for preparing a homogeneous anion exchange membrane, which is different from Embodiment 1 only in that, in step (1), the quaternization degree of the quaternized polyphenylsulfone is 10%; the other steps are consistent with Embodiment 1.
[0123] Example 7
[0124] This embodiment provides a method for preparing a homogeneous anion exchange membrane, which is different from Embodiment 1 only in that, in step (1), the quaternization degree of the quaternized polyphenylsulfone is 70%; the other steps are consistent with Embodiment 1.
[0125] Example 8
[0126] This embodiment provides a method for preparing a homogeneous anion exchange membrane, which differs from Embodiment 1 only in that, in step (2), the gradient temperature increase procedure is: first increase the temperature to 40°C and keep warm for 20 minutes, then increase the temperature to 70°C and keep warm for 15 minutes, and finally increase the temperature to 100°C and keep warm for 10 minutes; the other steps are consistent with Embodiment 1.
[0127] Example 9
[0128] This embodiment provides a method for preparing a homogeneous anion exchange membrane, which differs from Embodiment 1 only in that, in step (2), the gradient temperature increase procedure is: first increase the temperature to 80°C and keep it for 5 minutes, then increase the temperature to 100°C and keep it for 7 minutes, and finally increase the temperature to 120°C and keep it for 15 minutes; the other steps are consistent with Embodiment 1.
[0129] Example 10
[0130] This embodiment provides a method for preparing a homogeneous anion exchange membrane, which differs from Embodiment 1 only in that, in step (2), the gradient cooling procedure is: first cooling to 70°C and keeping warm for 20 min, then cooling to 40°C and keeping warm for 5 min; the other steps are the same as Embodiment 1.
[0131] Embodiment 11
[0132] This embodiment provides a method for preparing a homogeneous anion exchange membrane, which differs from Embodiment 1 only in that, in step (2), the gradient cooling procedure is: first cooling to 110° C. and keeping warm for 15 min, then cooling to 90° C. and keeping warm for 3 min; the other steps are the same as those in Embodiment 1.
[0133] Example 12
[0134] This embodiment provides a method for preparing a homogeneous anion exchange membrane, which is different from Embodiment 1 only in that, in step (2), a gradient cooling procedure is no longer performed, that is, after heating to 140°C and keeping warm for 1 min, it is directly taken out of the oven and cooled to room temperature to obtain the homogeneous anion exchange membrane; the other steps are consistent with Embodiment 1.
[0135] Comparative Example 1
[0136] This comparative example provides a method for preparing an anion exchange membrane, and the method for preparing an anion exchange membrane comprises the following steps:
[0137] (1) 200 g of polyphenylsulfone, 20 g of polyvinyl alcohol and 2000 g of N,N-dimethylacetamide were mixed and stirred at 40° C. for 20 h until they were completely dissolved to obtain a casting solution;
[0138] (2) Take 100 mL of casting solution and spray it evenly on the PET mesh (area 1000 cm 2 , thickness of 40 μm), to obtain a wet film;
[0139] (3) placing the wet film in an oven, setting a gradient heating and cooling program for curing, and then taking it out of the oven and cooling it to room temperature to obtain a dry film;
[0140] The curing treatment is as follows: heating to 50°C for 15 minutes, heating to 80°C for 7 minutes, heating to 120°C for 5 minutes; then cooling to 80°C for 7 minutes, cooling to 50°C for 15 minutes;
[0141] (4) The dried membrane sheet is immersed in a 20% by mass aqueous solution of trimethylamine for quaternization reaction for 24 hours, washed with deionized water, and placed in air to dry naturally at room temperature to obtain the anion exchange membrane.
[0142] Comparative Example 2
[0143] This comparative example provides a method for preparing an anion exchange membrane, and the method for preparing an anion exchange membrane comprises the following steps:
[0144] (1) 200 g of quaternized polyphenylsulfone with a quaternization degree of 20%, 20 g of polyvinyl alcohol and 2000 g of N,N-dimethylacetamide were mixed and stirred at 40° C. for 20 h until they were completely dissolved to obtain a casting solution;
[0145] (2) Take 100 mL of casting solution and spray it evenly on the PET mesh (area 1000 cm 2 , thickness of 40 μm), to obtain a wet film;
[0146] (3) The wet membrane sheet is placed in an oven, heated to 80° C. and subjected to a constant temperature curing treatment for 2 h, and then taken out of the oven and cooled to room temperature to obtain the anion exchange membrane.
[0147] Test Example 1
[0148] Test samples: the homogeneous anion exchange membranes provided in Examples 1 to 12, the anion exchange membranes provided in Comparative Examples 1 to 2, commercial membrane 1 and commercial membrane 2.
[0149] Test method: In addition to comparing the basic performance of the ion exchange membrane with two commercial ion exchange membranes, the membrane was concentrated using a homemade micro ED device in the laboratory (10 membrane pairs), and the initial NaCl concentration of the dilution and concentrate was 1mol / L. The membrane was compared with a commercial ion exchange membrane. When the operation time was the same and the concentration ratio was the same, the energy consumption of the prepared membrane and the commercial membrane was 612 and 573kwh / tNaCl respectively. When the operation time was the same and the concentration ratio was the same, the energy consumption of the prepared membrane and the commercial membrane was also compared.
[0150] The specific test results are shown in Table 1 below:
[0151] Table 1
[0152]
[0153] As shown in Table 1, the thickness of the homogeneous anion exchange membrane obtained by the preparation method of the present invention is 0.1-0.3 mm; the resistance of the homogeneous anion exchange membrane is 4.5-5 Ω·cm 2 ; The water content of the homogeneous anion exchange membrane is below 25%; the ion exchange capacity of the homogeneous anion exchange membrane is above 1.8 mmol / g; the bursting strength of the homogeneous anion exchange membrane is >0.50 MPa; the energy consumption of the homogeneous anion exchange membrane is 540-581 kwh / t·NaCl.
[0154] Thus fully illustrate, the method for preparing homogeneous anion exchange membrane used in the present invention, use novel quaternary aminated polymer as film precursor, use organic solvent dissolution, and add a certain amount of cross-linking agent after coating, then carry out gradient temperature rise and temperature reduction heat treatment to form film, the operation process is simple, easy to automatic control. The used film raw materials all have the characteristics of high stability and high strength, and the cross-linking agent added makes the whole material structure more tight and stable, so the prepared diaphragm has the advantage of high mechanical strength. And can be coated on the supporting mesh, further increase its mechanical strength. In addition, the cross-linking agent can form a tighter structure between the molecular chains of the polymer, thereby reducing the influence and destruction of the polymer molecular chains due to the external environment.
[0155] Test Example 2
[0156] Test samples: the homogeneous anion exchange membranes provided in Examples 1 to 12 and the anion exchange membranes provided in Comparative Examples 1 to 2.
[0157] Test method: The obtained ion membrane sample was immersed in 0.1M hydrochloric acid solution and 0.1M sodium hydroxide solution for 24 hours respectively, and repeated for 30 cycles to observe whether separation occurred between the coating on the surface of the ion membrane and the supporting layer.
[0158] The specific test results are shown in Table 2 below:
[0159] Table 2
[0160]
[0161]
[0162] As shown in Table 2, after the homogeneous anion exchange membrane prepared by the preparation method of the present invention is soaked in acid or alkali, no separation occurs between the coating on the membrane surface and the support layer.
[0163] This fully illustrates that the method for preparing anion exchange membrane of the present invention increases the cross-linking density of the membrane by using a novel quaternary ammonium polymer material and a cross-linking agent, thereby enhancing the structural stability of the membrane, reducing its swelling, improving the compatibility of the coating layer and the support layer, and thus improving the bonding between them. At the same time, a gradient heat treatment method of first heating up and then cooling down is used to prevent the membrane from deforming and cracking due to thermal expansion and contraction during the preparation process, so that the coating layer and the support layer are not easy to separate during long-term use, which significantly improves the stability of the membrane.
[0164] In summary, the method for preparing a homogeneous anion exchange membrane of the present invention has the following advantages:
[0165] 1. The membrane-making operation process is simple and the conditions are controllable: The method for preparing a homogeneous anion exchange membrane used in the present invention uses a quaternized novel quaternized polymer material mixed with a cross-linking agent as a membrane precursor, which is dissolved in an organic solvent and then coated. The membrane can be formed after heat treatment. The operation process is simple, the process complexity is reduced, the process repeatability is improved, and it is easy to automatically control.
[0166] 2. High mechanical strength: The method adopted by the present invention selects a new type of quaternized polymer with excellent mechanical properties, high strength and good impact resistance as the raw material for membrane making, and the functionalized sites are evenly distributed. In addition, the addition of a cross-linking agent promotes the formation of covalent bonds or ionic bonds between polymer molecules, making the structure of the ion membrane more stable, thereby enhancing its mechanical properties. And coating on the reinforcing mesh further increases the strength and has no significant effect on the conductivity of the membrane, extending the service life of the membrane and reducing the replacement frequency of the membrane.
[0167] 3. Low swelling, improved compatibility between the coating and the support layer: The method for preparing anion exchange membrane of the present invention increases the cross-linking density of the membrane through the new quaternary ammonium polymer material and the cross-linking agent, thereby enhancing the structural stability of the membrane, reducing its swelling, improving the compatibility between the coating and the support layer, and thus improving the bonding between them. At the same time, the gradient heat treatment method of first heating up and then cooling down is used to prevent the membrane from deforming and cracking due to thermal expansion and contraction during the preparation process, so that the coating and the support layer are not easy to separate during long-term use, which significantly improves the stability of the membrane.
[0168] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a homogeneous anion exchange membrane, characterized in that: The preparation method of the homogeneous anion exchange membrane comprises the following steps: The quaternized polymer, the cross-linking agent and the organic solvent are mixed to obtain a casting solution; Applying the casting solution on the support layer to obtain a wet film sheet; The wet membrane sheet is heat treated by a gradient temperature increase method to obtain the homogeneous anion exchange membrane.
2. The method for preparing a homogeneous anion exchange membrane according to claim 1, characterized in that: The casting solution comprises the following components by weight percentage: 10-60% of quaternary ammonium polymer, 0.1-10% of cross-linking agent, and the balance is organic solvent; Preferably, the quaternized polymer is selected from any one or a combination of at least two of quaternized polyetherketone, quaternized polyetheretherketone, quaternized polyetherketoneketone, quaternized polyetheretherketoneketone, quaternized polyetherketoneetherketoneketone, quaternized polysulfone, quaternized polyethersulfone, quaternized polyphenylsulfone or quaternized polyarylsulfone; Preferably, the degree of quaternization of the quaternized polymer is 10 to 60%; Preferably, the cross-linking agent is selected from any one or a combination of at least two of polyvinyl alcohol, polyvinyl pyrrolidone, divinyl benzene, formaldehyde, maleic acid or glutaraldehyde; Preferably, the organic solvent is selected from any one of dimethyl sulfoxide, 1,2-dichloroethane, N,N-dimethylformamide, N,N-dimethylacetamide, N-methyl-2-pyrrolidone, dichloromethane or chloroform, or a combination of at least two thereof.
3. The method for preparing a homogeneous anion exchange membrane according to claim 1, characterized in that: In the process of preparing the casting solution, the mixing temperature is 30 to 50° C., and the mixing time is 12 to 48 hours.
4. The method for preparing a homogeneous anion exchange membrane according to claim 1, characterized in that: The support layer includes any one of mesh, non-woven fabric or porous membrane; Preferably, the material of the support layer is selected from any one of polypropylene, polyethylene, polyvinyl chloride, polytetrafluoroethylene, polyethylene terephthalate, nylon or glass fiber; Preferably, the support layer has a thickness of 10 to 200 μm.
5. The method for preparing a homogeneous anion exchange membrane according to claim 1, characterized in that: The thickness of the wet film coated on the support layer is 0.2-1.0 mm.
6. The method for preparing a homogeneous anion exchange membrane according to claim 1, characterized in that: The program of the gradient heating is: First raise the temperature to 50-80℃ and keep it for 10-15min, then raise the temperature to 80-100℃ and keep it for 5-10min, and finally raise the temperature to 110-140℃ and keep it for 1-5min.
7. The method for preparing a homogeneous anion exchange membrane according to claim 1, characterized in that: After the heat treatment is completed, the following step further comprises: performing post-treatment on the heat-treated membrane by using a gradient cooling method; Preferably, the gradient cooling procedure is: First cool down to 80-100℃ and keep warm for 5-10 minutes, then cool down to 50-80℃ and keep warm for 1-5 minutes.
8. A homogeneous anion exchange membrane, characterized in that: The homogeneous anion exchange membrane is prepared by the method for preparing a homogeneous anion exchange membrane according to any one of claims 1 to 7.
9. The homogeneous anion exchange membrane according to claim 8, characterized in that The thickness of the homogeneous anion exchange membrane is 0.1 to 0.3 mm; Preferably, the resistance of the homogeneous anion exchange membrane is 2 to 5 Ω·cm 2 ; Preferably, the water content of the homogeneous anion exchange membrane is less than 25%; Preferably, the ion exchange capacity of the homogeneous anion exchange membrane is greater than 1.8 mmol / g; Preferably, the bursting strength of the homogeneous anion exchange membrane is greater than 0.50 MPa.
10. Use of the homogeneous anion exchange membrane according to claim 8 or 9 in preparing anion exchange membrane for electrodialysis.
Citation Information
Patent Citations
Monomer in situ polymerization-based homogeneous anion-exchange membrane and preparation method thereof
CN102179186A
Homogeneous-phase anion-exchange membrane and preparation method thereof
CN105903357A
Continuous preparation method of porous composite ion membrane
CN110120540A
Preparation method of anion exchange membrane
CN110560181A
Preparation method and application of homogeneous cation exchange membrane of anionic surfactant
CN113522043A